LAND RESOURCE MANAGEMENT STRATEGY FOR THE SUSTAINABILITY OF THE UPPER WATERSHED OF PALU (Case Study of Miu Sub Watershed in Sigi Regency) - Danang Widjajanto; Uswah Hasanah (Universitas Tadulako, 2019)
Population growth and regional expansion has increased land needs for settlement, agriculture, and trade in the Palu watershed causing much pressure on the upper part of the watershed where Miu watershed is situated The general aim of the research was to generate strategy for sustainable land resources management in the Miu watershed as a buffer zone of the Lore-Lindu National Park. The objective of the research were 1) to predict soil erosion and sedimentation, 2) to analyze the feasibility of dominant farming systems, 3) to analyze rural development, and 4) to analyze community preference on land use priority. The erosion and sedimentation, and feasibility research was conducted through soil survey and socio-economic approach. The rural development index was determined using secondary data taken from related institution such as demography, regional structure and infra structure, and industrial-trade condition. The preferential analysis of land use priority for 10 years ahead was done using focus group discussion with farmer community leaders. The soil erosion rate was light - heavy whilst the soil erosion index was low - very high estimated by the USLE. The relationship between the river debit and suspended load at the upper and lower part of the watershed was found to follow the equation of Y= 0.001X1.366 (R2= 0.65), and Y = 0.001 X1.409 (R2 = 0.66), respectively. Three villages included Pakuli, Pandere, and Bolapapu had high index of rural development whereas low index was found in Lonca, Bangga and Tangkulowi. The high-low order of land use priority was agro forestry, cacao monoculture, fresh water fishery, wetland rice, ruminant grazing, mixed culture of rice, soy bean, cassava and maize, and poultry farming.